Antimicrobial activity and metabolite profiling of a methanolic extract from Stereum rugosum - Bunga Anggreini Sari; Noverita; Ernawati Sinaga (Acta Scientiarum. Biological Sciences, 2025)
Although Indonesia is recognized as a global biodiversity hotspot, studies on macrofungi and their bioactive metabolites remain limited. This study evaluated the antimicrobial potential of macrofungi collected from Mount Halimun Salak National Park (MHSNP), Indonesia, focusing on species with strong antibacterial activity and their chemical profiles. Of the five species examined, Stereum rugosum exhibited the most potent effect. Its methanolic extract selectively inhibited Gram-positive bacteria, particularly Staphylococcus aureus and Streptococcus mutans, with minimum inhibitory concentrations (MIC) of 6.67 mg mL-1 and 13.33 mg mL-1, and minimum bactericidal concentrations (MBC) of 13.33 mg mL-1 and 26.67 mg mL-1, respectively. No activity was observed against Gram-negative bacteria or Candida albicans. Gas chromatography–mass spectrometry (GC-MS) analysis identified 22 compounds, primarily 2,5-cyclohexadiene-1,4-dione derivatives (24.22%), quinoline (17.07%), and methyl oleate (5.22%), which have all been associated with antimicrobial properties. This study is the first to report on the antimicrobial potential and chemical composition of S. rugosum from MHSNP. The selective inhibition of Gram-positive pathogens, especially S. aureus, establishes S. rugosum as a promising source of bioactive metabolites with potential pharmaceutical applications.